The Skeletal Morphology and Development of Rat (Rattus Norvegicus L.) Fetus which Given Feed Containing Pineapple (Ananas comosus Merr.) Peel during Pregnancy - Astuti, Ni Komang Frely; Setyawati, Iriani; Narayani, Inna (Metamorfosa: Journal of Biological Sciences, 2019)
Pineapple peel in animal feed might contain bromelain enzyme which could distrupt pregnancy in animal laboratory. This experiment used a complete randomized design with 16 pregnant rats which were divided into four treatment groups. The treatments are feed containing  0 (K); 4,35 (P1); 8,70 (P2); and 13,05 (P3) g/rat/day of pineapple peel that were given during pregnancy. Parameters of morphological fetus observed were alive fetuses, weight, length, and fetal abnormalities and  skeleton development i.e. axial skeleton (costal, sternebral, and vertebral bones) and appendicular skeleton (vertebra caudal, metacarpal and metatarsal bones). Data were analyzed by SPSS version 22, using One Way Anova or Kruskal Wallis . The result showed that fetuses from pregnant rats which administered with feed containing pineapple peel showed teratogenic effect. Fetal morphological abnormalities of the fetus is subcutaneous hemorrhage in were found at dose of 8,70 (P2) and dose of 13,05 (P3) g/rat/day. Feed containing pineapple peel could inhibit ossification of  apendicular skeleton  in vertebra caudal, metacarpal, and metatarsal.